Detecting tweet sentiment and sarcasm on online learning during covid-19 - Das, Shishir Kumar; Nisa, Khairun; Kabir, Razit; Tonni, Israt Jahan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.